Proanthocyanidin characterization and bioactivity of extracts from different parts of Uncaria tomentosa L. (Cat’s Claw) - Navarro Hoyos, Mirtha (2017)
Apart from alkaloids, bioactive properties of Uncaria tomentosa L. have been attributed to its phenolic constituents. Although there are some reports concerning low-molecular-weight polyphenols in U. tomentosa, its polymeric phenolic composition has been scarcely studied. In this study, phenolic-rich extracts from leaves, stems, bark and wood (n = 14) of Uncaria tomentosa plants from several regions of Costa Rica were obtained and analysed in respect to their proanthocyanidin profile determined by a quadrupole-time-of-flight analyser (ESI-QTOF MS). Main structural characteristics found for U. tomentosa proanthocyanidins were: (a) monomer composition, including pure procyanidins (only composed of (epi)catechin units) and propelargonidins (only composed of (epi)afzelechin units) as well as mixed proanthocyanidins; and (b) degree of polymerization, from 3 up to 11 units. In addition, U. tomentosa phenolic extracts were found to exhibit reasonable antioxidant capacity (ORAC (Oxygen Radical Absorbance Capacity) values between 1.5 and 18.8 mmol TE/g) and antimicrobial activity against potential respiratory pathogens (minimum IC50 of 133 µg/mL). There were also found to be particularly cytotoxic to gastric adenocarcinoma AGS and colon adenocarcinoma SW620 cell lines. The results state the particularities of U. tomentosa proanthocyanidins and suggest the potential value of these extracts with prospective use as functional ingredients.